Analysis of Factors Affecting Inequality in Indonesia - Wijaya, Meisha Fatma; Saragih, Elisa Clara; Manurung, Reneva; Sibarani, Juan Charlos; Nalamjra, Anisa Sanas (Journal of Economics, Management and Accounting (JEMA), 2024)
This research aims to determine the influence of GRDP, government expenditure, population density, investment, and open unemployment on the Gini ratio in Indonesia during the period 2014–2023. The analysis technique uses E-Views 12 by selecting the Error Correction Model (ECM). Based on the results of the analysis, it can be concluded that the variables GRDP, population density, open unemployment, and government expenditures have a partial effect on the Gini ratio. Meanwhile, the investment variable has no partial effect on GRDP. In the GRDP variables, population density, open unemployment, government expenditures, and investment have a simultaneous influence on the Gini ratio.